2022
DOI: 10.3390/tropicalmed7090211
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antifungal Susceptibility of Clinically Relevant Candida Species, Identification of Candida auris and Kodamaea ohmeri in Bangladesh

Abstract: Candida species are major fungal pathogens in humans. The aim of this study was to determine the prevalence of individual Candida species and their susceptibility to antifungal drugs among clinical isolates in a tertiary care hospital in Bangladesh. During a 10-month period in 2021, high vaginal swabs (HVSs), blood, and aural swabs were collected from 360 patients. From these specimens, Candida spp. was isolated from cultures on Sabouraud dextrose agar media, and phenotypic and genetic analyses were performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…This shows that there is an important change in the rate of resistance, which in our study reached 18%. Nevertheless, the majority of C. albicans isolates were azole susceptible, thus the observed resistance percentage is mainly attributed to the presence of C. auris , which agrees with previous studies ( Pfaller et al., 2019 ; Sathi et al., 2022 ). Furthermore, it is noteworthy that 25% of the C. parapsilosis isolates were resistant to FLC, which confirms the increase of resistance in this species ( Escribano and Guinea, 2022 ) (see Figure 5 ).…”
Section: Discussionsupporting
confidence: 91%
“…This shows that there is an important change in the rate of resistance, which in our study reached 18%. Nevertheless, the majority of C. albicans isolates were azole susceptible, thus the observed resistance percentage is mainly attributed to the presence of C. auris , which agrees with previous studies ( Pfaller et al., 2019 ; Sathi et al., 2022 ). Furthermore, it is noteworthy that 25% of the C. parapsilosis isolates were resistant to FLC, which confirms the increase of resistance in this species ( Escribano and Guinea, 2022 ) (see Figure 5 ).…”
Section: Discussionsupporting
confidence: 91%
“…This shows that there is an important change in the distribution and rate of resistance, which in our study reached 18%. Nevertheless, the majority of C. albicans isolates were azole susceptible, thus the observed resistance percentage is mainly attributed to the presence of C. auris, which agrees with previous studies [35,40]. Furthermore, it is noteworthy that 25% of the C. parapsilosis isolates were resistant to FLC, which confirms the increase of resistance in this species Figure 5 [41].…”
Section: Discussionsupporting
confidence: 89%
“…According to the 22 publications of C. auris infection, comprising 256 children [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], reviewed herein, the most common type of invasive infection was bloodstream infection (94%, 194/206 patients with available data on the infection site) ( Table 3 and Table S1 ). The duration of candidemia was not reported in most studies and was available for only seven patients; the duration ranged between 7 and 11 days [ 16 , 20 , 36 ].…”
Section: Clinical Spectrum Of C Auris Infectionmentioning
confidence: 99%
“…Following exclusion of suspected repetitive studies, the search yielded 23 publications that reported C. auris incidents in children [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Twelve publications included both adult and pediatric patients [ 17 , 19 , 20 , 23 , 24 , 26 , 27 , 28 , 32 , 35 , 36 , 37 ]; of them, one did not provide specific details of the pediatric patients and was excluded [ 26 ]. Six provided limited specific details of the pediatric patients [ 17 , 19 , 24 , 27 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation